The Impact of an Algorithm-Guided Management of Preoperative Anemia in Perioperative Hemoglobin Level and Transfusion of Major Orthopedic Surgery Patients. (27th March 2013) - Enko, Dietmar; Wallner, Franz; von-Goedecke, Achim; Hirschmugl, Christa; Auersperg, Vinzenz; Halwachs-Baumann, Gabriele
Abstract : The aim of this study was to evaluate a laboratory-guided therapeutic algorithm of preoperative anemia. 335 patients with elective hip or knee arthroplasty were included in this retrospective before-after study. Group I (n =   101 ) underwent conventional preoperative procedures before algorithm implementation. Group II (n =   234 ) underwent algorithm-guided preoperative anemia management. A hemoglobin-level of 13 g/dL was the therapeutic cut-off for men and women. Reticulocyte hemoglobin content (CHr) and soluble transferrin receptor (sTfR)/log ferritin ratio were used in the form of the Thomas plot. Iron deficiency (ID) was substituted with 1000 mg iron intravenous (i.v.) and 10000 international units (I.U.) of erythropoiesis-stimulating agent (ESA) subcutaneous (s.c.) or i.v., anemia of chronic disease (ACD) (without functional ID) with 40000 I.U. ESA s.c. or i.v and additionally 200 mg iron i.v. Substituted anemic patients in Group II (n = 32 ) showed a distinctly higher preoperative (Hb-median 13 versus 11.95 g/dL) (P < 0.01 ) and postoperative (Hb-median 9.75 versus 9.0 g/dL) (P < 0.05 ) Hb level compared with untreated anemic patients in Group I (n = 24 ). In Group II red blood cell (RBC) units (35 units/234 patients) were reduced by 44% compared with Group I (27 units/101 patients). Algorithm-guided preoperative anemia management raises perioperative Hb-level and reduces blood use.